Between Borders and Bodies: Sovereignty, Universality, And The Crisis of Enforcement in International Law - Hassanien, Aliaa Riad, Aliaa Riad (AUC Knowledge Fountain, 2026)
Atrocities such as genocide and war crimes persist not despite international law, but within its very structure. Although international law is designed to protect humanity, it repeatedly fails to do so due to its inability to enforce its most fundamental norms. In the absence of enforcement, the law exists—but merely stands still. This failure stems from the structural contradictions embedded in the system—specifically, the tension between the principles of sovereignty and universality. As a result, international law has become a selective, politicized, and ineffective framework. Incidents such as the Rwandan genocide and the civil wars in Syria and Sudan demonstrate the extent of this malfunction. Even with the evolution of international law’s tools and enforcement mechanisms, these instruments have operated inconsistently, highlighting the selectivity and politicization that affect both the enforcement of rulings, as in the ICC and ICJ, and decisions regarding intervention as seen in the Responsibility to Protect principle. In contrast, Islamic law has offered governing principles that enhance accountability. The very definition of sovereignty in Islam, along with the Caliphate governance system—as opposed to the state-consent-dependent model—have fostered communal responsibility and entrenched decentralized authority, embedding accountability within the collective. Thus, comparative studies can help reimagine enforcement models in international law—models that are capable of combating impunity. Reconceptualizing the two core principles of international law—sovereignty and universality—may offer a path toward empowering the system.